Damage levels caused by Capulinia linarosae Kondo & Gullan (Hemiptera: Eriococcidae) on guava crops under two agronomic management practices in the south of Lake Maracaibo, Venezuela (2020)
The objective of the present study was to test the hypothesis of no difference in the level of damage caused by the guava cottony scale Capulinia linarosae (Hemiptera: Eriococcidae) in two guava crops under different agronomic management practices; a crop with organic management practices (PUA) was compared with another subjected to chemical methods (PUB). Forty plants on each farm were selected randomly to estimate damage on the stems, branches, leaves, and fruits. The levels of damage were statistically different (P<0.0001) between the methods for the stems and branches but not for the leaves or fruits (P>0.05). It was concluded that the magnitude of damage was greater in the crop under chemical control and that agronomic management was a critical factor. Excess insecticides and incorrect pruning applications cause damage to plant bark and favor insect proliferation. While the use of a sulfur-calcium broth in PUA regulated pH, it favored the effect of other products and promoted the growth of green algae, which covered bark crevices and inhibited cottony scale establishment. The excessive use of agrochemicals for weed control in PUB caused soil nudity and killed natural enemies, whereas, in PUA, the grass layer was clipped at 20 cm from the soil, maintaining moisture and creating a favorable habitat for natural enemies.